Integrating metacognitive strategies impact in virtual science experiments for undergraduate students’ HOTS - Trikinasih Handayani; Butch O. Saulon; Ika Maryani (LPMPP Universitas Negeri Yogyakarta, 2023)
Higher Order Thinking Skills (HOTS) are essential variables that support the achievement of science learning objectives. However, distance learning during the Covid-19 Pandemic was the cause of the lack of maximum HOTS for undergraduate science students due to their lack of involvement in experiments. Therefore, this study aims to apply a metacognition-integrated science virtual experiment model and examine its impact on students' HOTS science. A quasi-experiment was involved with a randomized pretest-posttest comparison group design to see the impact of the implementation of this model. Participants in the two treatment groups were randomly selected from two private universities in Indonesia. The HOTS of participants were assessed using multiple-choice questions. Observation sheets were used to measure the implementation of the learning model being developed. A general linear model with MANOVA was used to test the effect of the model, while Partial Eta Squared was used to measure the effect size of the model on HOTS. The results showed that the virtual science experimental model integrated with metacognition strategies significantly affected students' HOTS. The effect size measurement shows a high effect in the experimental group. Researchers recommend that universities apply a similar model to encourage students' achievement of HOTS.